Intervención psicopedagógica basada en las dinámicas de grupo para el desarrollo de habilidades sociales en un niño con síndrome de Down de quinto grado de la unidad de educación básica especializada Padre Franco Aguirre, cantón Calvas periodo 2022-2023 - Vega Condolo, Katherine Fernanda (2023)
The present curricular integration work had the general objective of implementing a Psychopedagogical intervention based on group dynamics for the development of social skills in a fifth grade boy with Down syndrome from the Father Franco Aguirre Specialized EGB Unit, Calvas canton. It was a case study, with a qualitative approach, descriptive type; For the collection of information, the psychopedagogical sheet and achievement sheet, semi-structured interview, the SECHS scale and an evaluation grid were used. The results obtained through the interviews describe that in the family context the child presents basic social skills (SA), very effusive with inappropriate attitudes; In the school context, he shows little empathy, shyness and does not interact. On the SECHS scale, the social skills of the child with DS have a percentage that varies between 20% and 40%, respectively, in each category of the three SA components; It was determined through the interview that teachers use activities such as relaxation and stimulation in emotional expression; Based on these results, a psychopedagogical intervention guide was designed based on group dynamics structured by 24 sessions. After evaluating the psychopedagogical intervention, the results show that social skills increased in percentage, reaching 40% and 60%. It is concluded that the SA of the child in the family and school context are not appropriate due to their effusive attitudes at home and asocial at school; likewise, the three components of SA are at levels that are not adequate and not adequate; teachers do not handle activities to develop SA, they only refer to relaxation and emotional control sporadically; The psychopedagogical intervention guide based on group dynamics was effective in the development of social skills.